A comparative study of three conservative treatments in patients with lumbar spinal stenosis: lumbar spinal stenosis with acupuncture and physical therapy study (LAP study) - Hiroyuki Oka; Ko Matsudaira; Yuichi Takano; Daichi Kasuya; Masaki Niiya; Juichi Tonosu; Masayoshi Fukushima; Yasushi Oshima; Tomoko Fujii; Sakae Tanaka; Hirohiko Inanami (BMC, 2018)
Abstract Background Although the efficiency of conservative management for lumbar spinal stenosis (LSS) has been examined, different conservative management approaches have not been compared. We have performed the first comparative trial of three types of conservative management (medication with acetaminophen, exercise, and acupuncture) in Japanese patients with LSS. Methods Patients with L5 root radiculopathy associated with LSS who visited our hospital for surgical treatment were enrolled between December 2011 and January 2014. In this open-label study, patients were assigned to three treatment groups (medication, exercise, acupuncture) according to the visit time. The primary outcomes were Zurich claudication questionnaire (ZCQ) scores before and after 4 weeks of treatment. Least square mean analysis was used to assess the following dependent variables in the treatment groups: changes in symptom severity and physical function scores of the ZCQ and the ZCQ score of patient's satisfaction after treatment. Results Thirty-eight, 40, and 41 patients were allocated to the medication, exercise, and acupuncture groups, respectively. No patient underwent surgical treatment during the study period. The symptom severity scores of the ZCQ improved significantly after treatment in the medication (p = 0.048), exercise (p = 0.003), and acupuncture (p = 0.04) groups. The physical function score improved significantly in the acupuncture group (p = 0.045) but not in the medication (p = 0.20) and exercise (p = 0.29) groups. The mean reduction in the ZCQ score for physical function was significantly greater for acupuncture than for exercise. The mean ZCQ score for treatment satisfaction was significantly greater for acupuncture than for medication. Conclusions Acupuncture was significantly more effective than physical exercise according to the physical function score of the ZCQ and than medication according to the satisfaction score. The present study provides new important information that will aid decision making in LSS treatment. Trial registration This study was registered with the UMIN Clinical Trials Registry ( UMIN000006957 ).